Model of a Safety Management System through Continuous Improvement (PDCA) for Artisanal Mining - Arteaga-Romani, Luis (2023)
Accidents occurring in artisanal mining are a growing problem. In 2021, MINEM presented the latest record of accidents that occurred in mining, with 63 fatal accidents. The limited information is due to a deficiency in formalizing these activities, which is a highly complex variable that affects the development of their operations. For this reason, it is important to analyze the direct causes of accidents in order to establish preventive measures that enable workers to carry out their tasks safely. The research proposal aims to reduce safety rates through a new methodology comprised of a series of actions, placing greater emphasis on accidents occurring in pit exploitation through the creation of a Safety Management System (SMS) based on the Plan-Do-Check-Act (PDCA) cycle. To achieve this, a study of accidents that have occurred in critical areas of artisanal mining over the past 5 years is conducted, where the risk level will be classified based on Hazard Identification, Risk Assessment, and Control (HIRAC) in order to propose control measures.